Hubungan Pengetahuan, Sikap PHBS terhadap Personal Hygine pada Anak Panti Asuhan Vincentius - Ernawaty Tamba; Bryan Simanjuntak; Wynda Muljono; Feby Siburian; Izyanie Ain; Erma Mexcorry Sumbayak (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
In 2014 the realization of PHBS household indicators on personal hygiene in Indonesia was 56.6% lower than the target of 70% with the realization of PHBS household indicators in DKI Jakarta Province of 69.3%. East Jakarta is the area with the lowest percentage of clean and healthy households, which is 33.9% of the 243,438 households monitored. This study was to determine the relationship between knowledge, clean and healthy living behavior and personal hygiene behavior at the Vincentius Orphanage for the period of June 2021. This study used a descriptive-analytic research design with a cross-sectional approach. Questionnaires were distributed and 42 respondents were taken using consecutive sampling technique. The results showed that there was a significant relationship between attitudes towards personal hygiene behavior with p value = 0.014. In addition, there is a significant relationship between the level of knowledge on personal hygiene behavior with a p value = 0.046. While the factors that did not have a significant relationship with personal hygiene behavior were the age and gender of the orphanage children. There is a significant relationship between attitude and level of knowledge on personal hygiene behavior in children at the Vincentius Orphanage in East Jakarta.